Study on suitability assessment method of vegetation restoration species in disturbed sites of transmission line engineering construction - Jang, Shixiong; Li, Xi; Wang, Lin; Wang, Chongqing; Chen, Yao; Su, Wei; Wei, Xiaochuan (Journal of Environmental Engineering and Landscape Management, 2025)
Screening species that can adapt to the disturbed habitats resulting from transmission line construction is of great practical significance for the ecological restoration of primary vegetation degradation caused by such construction. Therefore, a suitability evaluation method for vegetation restoration species in disturbed areas of transmission line engineering construction is studied to improve the ecological restoration. Based on the principles of stability and durability, adapting to local conditions and trees, and comprehensive and dominant screening, an index system for evaluating the adaptability of vegetation restoration species is established. Determine the subjective weight of evaluation index by G1 method and G2 method. The objective weight of evaluation index is determined by improving entropy weight method and deviation method. Through the optimal combination weighting method, the final evaluation index weight is obtained by combining subjective weight and objective weight. Using cloud model combined with index weight to calculate the certainty of each index. According to the principle of maximum certainty, the evaluation grade corresponding to the maximum certainty is selected as the final suitability evaluation result. The experiments have demonstrated that the suitability evaluation index system of this method exhibits high reliability, and it can effectively determine the weights of the suitability evaluation indices and complete the suitability assessment for vegetation restoration species. Among these species, Elymus chinensis, Panicum miliaceum, Brassica napus, arugula, and rye exhibit the most promising ecological restoration effects.